O seminário na escola: ensino e análise do gênero - Melo, Josiane da Silva (2020)
This work arose from our concerns with the insufficient space given to the oral modality in classrooms, as well as the lack of orientation and organization in the development of this practice, especially when we consider the school seminar, which is the focus of our research. Due to that, we aim to contribute to the development of oral production in classrooms and to a reflection upon this activity. We do that by means of the analysis of a didactic intervention based on school seminars in a ninth level group of middle school. This research is relied on the theoretical conceptions of Bakhtin (2011), Marcuschi (2002; 2007; 2008; 2010), Schneuwly (2004), Travaglia (2013), Bronckart (1999). It is also based on the PCNs (1997) regarding the studies of Orality applied to the didactic model made by Dolz et.al.(2004). This study is qualitative research to analyze the results of an action research which consisted in the application of the didactic sequence for school seminars proposed by Dolz, Noverraz and Schneuwly (2004). The corpus is consisted of transcript recordings from the seminar presentations, in which we attempted to analyze the possible influence of the producing conditions of the elaboration and presentation of seminars, as well as the students’ appropriation of their internal organization and their linguistic properties. The analysis reveals that part of the difficulties of the students is imposed by the context of the production of seminars. Due to that, teachers should intervene as always as possible to make the most positive of the actions related to the condition and production of seminars. The analysis also shows that the seminar genre structure and its linguistic properties were partially achieved by the students. Frequently, these properties emerged in an inappropriate manner, lacking formal and linguistic elements which are crucial to the comprehension and progression of the text. Considering that, we recognize the importance of a systemic teaching of the school seminar, in which the students could be exposed not only to the thematic content, but also to the compositional structure and linguistic construction, which we consider to be extremely relevant to the study of the genre